Down with the fascist attempts to suppress the Indian people's patriotic sentiments!!! - Hindustani Ghadar Party - Organization of Indian Marxist - Leninists Abroad:::Creator::::::::::::
This pamphlet addresses the poor living and working conditions of Indian workers and peasants in the 1970s and calls for revolution.